The effect of exercise on vaccine-related pain, anxiety and fear during HPV vaccinations in adolescents. Issue 23 (31st May 2018) - Lee, V.Y.; Booy, R.; Skinner, R.; Edwards, K.M.
Highlights: The World Health Organization (WHO) recently endorsed research to identify possible interventions to reduce vaccine-related pain in mass clinical and school-based settings. In particular, the lack of research in adolescent populations was highlighted. Exercise has been used as a behavioural adjuvant to vaccines, and is also known to have acute analgesic effects. The aim of the study was to examine the effect of exercise on vaccine-related pain, anxiety and fear in adolescents (11–13 years old) during routine school-based HPV vaccination program. This study is, to our knowledge, the first to demonstrate that a short bout of exercise prior to injection decreases vaccine-related pain in female adolescents. Abstract: Introduction: With increased school-based vaccinations for improved coverage rates and practicality, the World Health Organization (WHO) recently endorsed research to identify possible interventions to reduce vaccine-related pain in mass clinical and school-based settings. In particular, the lack of research in adolescents indicate a particular need in this population. Acute exercise has analgesic effects and has been used as a behavioural adjuvant to vaccination. Here, we examine the effect of exercise on vaccine-related pain, anxiety and fear in adolescents, during a school-based program for HPV vaccinations. Methods: 116 students (Female: 61, Male: 55) aged 11–13 years were randomly allocated to either an Exercise (n = 60) or Control (n = 56) group. All participants completed demographic and Trait-anxiety questionnaires prior to receiving the vaccine according to usual care. The Exercise group also performed upper body exercise for 15 min prior to receiving the vaccine. Immediately after the vaccine administration, all participants reported on pain, anxiety and fear at the time of receiving the vaccine. Results: Female adolescents in the Exercise group reported significantly less pain (3.64; 95% CI, 2.98–4.30) than Controls (4.58; 95% CI, 3.96–5.19; p = 0.04). Further, females reported greater pain and anxiety than males in the Control group but not the Exercise group. Conclusion: This study supports the use of exercise prior to vaccine administration, especially in female adolescents who are particularly vulnerable to negative experiences during vaccination procedures. Furthermore, the ease of application, as well as the benefit of exercise, provides support for the use of simple exercise prior to vaccination in mass vaccination settings. Clinical trial registry : ANZCTR, ACTRN12614001185651.